The game of method: board games as support for teaching research courses - Almeida, Felipe Drude (2017)
This article proposes a board game to support the teaching of the principles of scientific research. Its methodology involves literature review, game testing, and game design. Its objective is to define good practices for the use of these games (analog or digital) in the teaching of Scientific Methodology. The literature review identified some board games developed for this purpose: Snakes and Ladders, Defense of Hidgeon, The Game of Research and Cheats and Geeks. These games were evaluated through several game design and educational design categories, such as narrative, usability/interface, mechanics, gameplay, art/aesthetics, learning, sound, balance between entertainment/education and time to play. The article suggests good practices for the design of educational board games and presents the proposal of a board game for the teaching of scientific methodology.